Hydroxypropyl Cellulose/Pluronic-Based Composite Hydrogels as Biodegradable Mucoadhesive Scaffolds for Tissue Engineering - Daniela Filip; Doina Macocinschi; Mirela-Fernanda Zaltariov; Bianca-Iulia Ciubotaru; Alexandra Bargan; Cristian-Dragos Varganici; Ana-Lavinia Vasiliu; Dragos Peptanariu; Mihaela Balan-Porcarasu; Mihaela-Madalina Timofte-Zorila (Gels, 2022)
Recently, the development of new materials with the desired characteristics for functional tissue engineering, ensuring tissue architecture and supporting cellular growth, has gained significant attention. Hydrogels, which possess similar properties to natural cellular matrixes, being able to repair or replace biological tissues and support the healing process through cellular proliferation and viability, are a challenge when designing tissue scaffolds. This paper provides new insights into hydrogel-based polymeric blends (hydroxypropyl cellulose/Pluronic F68), aiming to evaluate the contributions of both components in the development of new tissue scaffolds. In order to study the interactions within the hydrogel blends, FTIR and 1HNMR spectroscopies were used. The porosity and the behavior in moisture medium were highlighted by SEM and DVS analyses. The biodegradability of the hydrogel blends was studied in a simulated biological medium. The hydrogel composition was determinant for the scaffold behavior: the HPC component was found to have a great influence on the BET and GAB areas, on the monolayer values estimated from sorption–desorption isotherms and on mucoadhesivity on small intestine mucosa, while the Pluronic F68 component improved the thermal stability. All blends were also found to have good mechanical strength and increased biocompatibility on the NHDF cell line. Based on their particular compositions and increased mucoadhesivity on small intestine mucosa, these polymeric blends could be effective in the repair or recovery of damaged cell membranes (due to the contribution of Pluronic F68) or in control drug-delivery intestinal formulations.